A Comparative Study of Financial Performance Between Conventional and Islamic Banking in United Arab Emirates - Ibrahim, Mukdad (International Journal of Economics and Financial Issues, 2015)
The purpose of this study is to compare the financial performance of two UAE based Islamic and conventional banks between the years 2002 and 2006. Quantitative analysis was undertaken by looking at various sets of financial ratios that are routinely used to measure bank performance. The main ratios that were employed put a particular focus on the banks liquidity, profitability, management capacity, capital structure and share performance as reliable indicators of a bank performance. Descriptive statistical analysis was used to rank the performance, measuring the dispersion and the stability-variability of the indicators. The research goes one step further and measures the financial stability of the two banks. Conclusions were then drawn from the computation of the relevant ratios that allowed the author to make an effective comparison of said banks. Subsequently, each bank’s performance was then ranked via the use of descriptive statistical analysis. This type of analysis was used to summarize the performance of each bank based on three criteria, mean, coefficient of variation and the overall stability of each banks performance. The findings showed that both banks performed reasonably well during the period studied. While the bank of Sharjah benefitted by having an overall higher degree of liquidity, profitability, management capacity and capital structure, Dubai Islamic bank was better off in relation to share indicators performance and in terms of overall stability. Keywords: Banking; Financial Analysis; Performance Measurement; Financial Ratios; United Arab Emirates JEL Classifications: E44; G21; M40